2012
DOI: 10.1177/2042018812458697
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for the metabolic syndrome in schizophrenia: a review

Abstract: Abstract:The metabolic syndrome (MetS) is an increasingly prevalent condition in people with schizophrenia. It remains highly prevalent in the general population in developed countries, but recently health promotion campaigns and greater awareness of the high associated mortality rates have resulted in improvements in the rates of cardiovascular risk factors. This is not the case for people with schizophrenia who continue to have more than twice the rates of MetS and significantly higher mortality rates than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 131 publications
0
41
0
4
Order By: Relevance
“…Nadalje, studije koje su istražile učinak antipsihotičnih lijekova na pojedinačne komponente metaboličkog sindroma ukazuju da je terapija antipsihoticima povezana s čak 6 -55 %-tnom prevalencijom prekomjerne tjelesne mase i pretilosti, 2 -28 %-tnom prevalencijom dijabetesa tipa 2, prevalencijom dislipidemije od 15 -53 % te hipertenzije od 16 -49 % 33 . Uočeno je da politerapija antipsihotičnim lijekovima i, kao što je već spomenuto, upotreba atipič-nih antipsihotika (antipsihotičnih lijekova druge generacije) posebice pridonose razvoju metaboličkih abnormalnosti 6,34 . Atipični antipsihotici, za razliku od tipičnih antipsihotičnih lijekova, posjeduju veći afinitet za serotoninske 5-HT2 receptore, negoli dopaminske D2 receptore, brže disociraju s dopaminskih D2 receptora, a mnogi od njih su se pokazali i potentnim blokatorima histaminskih H1 receptora te receptora drugih neurotransmiterskih sustava.…”
Section: Povezanost Terapije Antipsihotičnim Lijekovima S Metaboličkiunclassified
See 1 more Smart Citation
“…Nadalje, studije koje su istražile učinak antipsihotičnih lijekova na pojedinačne komponente metaboličkog sindroma ukazuju da je terapija antipsihoticima povezana s čak 6 -55 %-tnom prevalencijom prekomjerne tjelesne mase i pretilosti, 2 -28 %-tnom prevalencijom dijabetesa tipa 2, prevalencijom dislipidemije od 15 -53 % te hipertenzije od 16 -49 % 33 . Uočeno je da politerapija antipsihotičnim lijekovima i, kao što je već spomenuto, upotreba atipič-nih antipsihotika (antipsihotičnih lijekova druge generacije) posebice pridonose razvoju metaboličkih abnormalnosti 6,34 . Atipični antipsihotici, za razliku od tipičnih antipsihotičnih lijekova, posjeduju veći afinitet za serotoninske 5-HT2 receptore, negoli dopaminske D2 receptore, brže disociraju s dopaminskih D2 receptora, a mnogi od njih su se pokazali i potentnim blokatorima histaminskih H1 receptora te receptora drugih neurotransmiterskih sustava.…”
Section: Povezanost Terapije Antipsihotičnim Lijekovima S Metaboličkiunclassified
“…U odnosu na tipične antipsihotike, pripisuje im se značajno manje ekstrapiramidnih nuspojava, manji učinak na poviše-nje koncentracije prolaktina, kao i superiorniji učinak u terapiji, posebice kod negativnih i kognitivnih simptoma 35,36 . Ipak, istraživanja ukazuju na gotovo trostruko veću učestalost metaboličkog sindroma u pacijenata koji su uzimali atipične antipsihotike u usporedbi sa skupinom oboljelih čija je terapija uključivala isključivo tipične antipsihotične lijekove (28 % vs. 10 %) 29,34 . Nadalje, čini se da klozapin i olanzapin najviše od svih antipsihotičnih lijekova pridonose riziku za nastanak meta-S. Nadalin, M. Gudeljević, J. Severec et al: Etiopatogeneza metaboličkog sindroma u shizofreniji -najnovije spoznaje medicina fluminensis 2017, Vol.…”
Section: Povezanost Terapije Antipsihotičnim Lijekovima S Metaboličkiunclassified
“…Study design, content of interventions, and measured outcomes vary greatly (Pearsall et al, 2014, Bonfioli et al, 2012. Likewise, they have included participants with different psychiatric diagnoses, for instance, persons with psychosis (Bonfioli et al, 2012), schizophrenia (Papanastasiou, 2012), mental Illness (Happell et al, 2012), or serious mental illness (Lowe and Lubos, 2008), which may hamper the possibility to compare results between studies (Fernández-San-Martín et al, 2014). Lowe and Lubos (2008) have called for more research with standardized outcome measures to determine and compare the effectiveness of educational and exercise intervention, with usual treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Pearsall et al, 2014, Bonfioli et al, 2012, Happell et al, 2012, Papanastasiou, 2012, Lowe and Lubos, 2008 have demonstrated a great variety of lifestyle interventions for persons with psychosis. In the absence of convincing research findings, there is no consensus or "golden standard" of lifestyle interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews suggest positive impacts on weight loss, BMI, glucose tolerance etc. [7,8].…”
Section: Introductionmentioning
confidence: 99%